Management of Potato Bacterial Wilt Disease Using Abiotic Treatments - Mostafa , Hanan S; khalifaa, Hanan A.; Elsyd, Wafaa M.; Abdel-Ghaffar N.Y. (Al-Mukhtar Journal of Sciences, 2022)
Bacterial wilt disease caused by Ralstonia solanacearum (Smith) Yabuuchi is one of the most important bacterial diseases in the world. This study aimed to test some chemical compounds such as bactericides that were applied to control bacterial wilt disease under artificial inoculation conditions and their effects on the yield of potatoes under greenhouse conditions.In vitro, tested chemical compounds (Cefalexin, Gentamycin, and Copper sulphate) inhibit the growth of R. solanacerum compared with control treatment. Copper sulphate was the most effective where the Inhibition zone diameter was 6.0 to7.4mm compared with cefalexin and gentamycin, 3.6 to 5.8mm respectively, but cefalexin was moderately effective 4.2 to 5.8mm and gentamycin was less effective 3.6 to 5.8mm against the pathogen. Inhibition zone diameter was increased with increasing concentrations of tested chemical compounds. Greenhouse experiments showed that the chemical compounds used reduced the severity of potato bacterial wilt disease and increased potato yield compared with control treatment. When using Cefalexin, the mean of wilted shoots was 20.5 and the severity of disease 16.3, while when using Gentamycin as an Abiotic, the mean of wilted shoots was 22.8 and severity of disease 17.6 which was the most effective compared with Copper sulphate treatment were wilted shoot was 31.8 and severity of disease 29.6. The application of tested chemical compounds as soil drench treatment led to a percentage of infection which ranged from16.4 to19.0 more effective than tuber treatment where the percentage of infection ranged from 18.4 to 20.1.